The inner pulse unlocking the secret code of sickness and health - Siegel, Marc (Marc K.) (John Wiley & Sons, 2011)
"Understanding the secret code of illness and health Many doctors overlook the seemingly inexplicable tragedies and recoveries that happen in hospitals every day, opting to view them simply as aberrations from the medical norm. In this book, Dr. Marc Siegel draws from his decades of experience treating patients and explores the sometimes miraculous effects that the spirit and emotion can have on disease and healing. The inner pulse is the essence that links the soul to the mind and body, the marker that predicts whether a person's life force is fading or strengthening. This book shows you how to tap into your inner pulse and even how to influence it. Explores how your inner pulse can alert you to what is going on in your body Offers a new perspective on the positive and negative effects of the mind on illness and healing Includes dramatic case stories of Dr. Siegel's work with his own patients those who have healed and those who have not Exploring the uncanny world where expectation and outcome are driven by a patient's personal intuition, this book will give you a deeper understanding of how the mind relates to disease and how the mind and the body working in sync can help heal."--Provided by publisher.